Implementation of Character Education and Improvement of Skill Writing Descriptive in Class 4 SDN 075043 Oladano - Feberlina Hura; Neviyarni S; Taufina Taufik (Universitas Negeri Padang, 2018)
This article was written to describe the implementation of character education in the fourth grade of SDN 075043 OladanoIdanogawo Sub-district during the pre-writing, writing and post-writing stages. Based on the results of the research, the students' skill results are obtained at the following stages: 1) pre-writing with an average of 7.55 and 62.92% percentage included enough category, cycle II obtained an average of 9.45 with a percentage of 78.85% including good category. 2) Writing with an average of 7.65 and 63.0% percentage including enough category. Cycle II average of 9.45 with percentage of 79% including good category. 3) Post-Writings obtained an average of 8.15 with percentage of 68% including enough category, cycle II post-writing with average 9.65 with percentage of 80.4% including good category.